Effectiveness of non-operative approaches in active enamel carious lesions: a retrospective longitudinal study - Andressa da Silva ARDUIM; Debora Plotnik GONÇALVES; Maitê Munhoz SCHERER; Fernando Borba de ARAÚJO; Tathiane Larissa LENZI; Luciano CASAGRANDE (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of the study was to investigate the effectiveness of non-invasive and micro-invasive treatments in active enamel carious lesions in high-caries-risk children. Clinical records of children treated in a dental school setting were retrospectively screened for active enamel carious lesions treated non-invasively (topical fluoride applications, oral hygiene instruction, or dietary guidance) or micro-invasively (sealant). The control of active carious lesions was set as the main outcome established by the combination of inactivation and non-progression of the lesions based on Nyvad and ICDAS criteria, respectively. Individual and clinical factors associated with the outcome were analyzed by Poisson regression. The sample consisted of 105 high-caries-risk children with a mean age of 8.3 (± 2.4) years. From a total of 365 active enamel carious lesions, most lesions (84.1%) were active non-cavitated carious lesions (ICDAS scores 1 and 2) and only 15.9% presented localized enamel breakdown (ICDAS score 3). Of these, 72.6% were inactivated and 92.1% did not progress (mean time of 6.5 ± 4.1 months). The prevalence of controlled carious lesions was higher among children older than 6 years (PR:1.43; 95%CI:1.00-2.03; p = 0.04) and in those with better biofilm control (PR:0.99; 95%CI: 0.98-0.99; p = 0.03). Non-operative approaches are effective for controlling active enamel carious lesions. The majority of active enamel carious lesions became inactive and did not progress after treatment. Caries control was associated with older children and better biofilm control.